2004
DOI: 10.1124/jpet.104.077669
|View full text |Cite
|
Sign up to set email alerts
|

Dual, Hyperalgesic, and Analgesic Effects of the High-Efficacy 5-Hydroxytryptamine 1A (5-HT1A) Agonist F 13640 [(3-Chloro-4-fluoro-phenyl)-[4-fluoro-4-{[(5-methyl-pyridin-2-ylmethyl)-amino]-methyl}piperidin-1-yl]methanone, Fumaric Acid Salt]: Relationship with 5-HT1A Receptor Occupancy and Kinetic Parameters

Abstract: The aim of the present study was to establish the relationship between the plasma and brain concentration-time profiles of F 13640-yl]methanone, fumaric acid salt] after acute administration and both its hyper-and hypoanalgesic effects in rats. The maximal plasma concentration (C max ) of F 13640 after i.p. administration of 0.63 mg/kg was obtained at 15 min and decreased to half its maximal value after about 1 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Male Sprague‐Dawley rats weighing 160–180 g upon arrival were group‐housed (five animals per cage) with free access to food and water. The formalin test was carried out as described by Bardin et al. (2005).…”
Section: Methodsmentioning
confidence: 99%
“…Male Sprague‐Dawley rats weighing 160–180 g upon arrival were group‐housed (five animals per cage) with free access to food and water. The formalin test was carried out as described by Bardin et al. (2005).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that 5-HT1A receptor is one of the major subtypes distributed in the dorsal horn of the spinal cord (Lopez-Garcia, 2006). As for the functions of 5-HT1A in the spinal cord dorsal horn, some reports suggest its involvement in mediation of nociception (Zhang et al, 2001; Lindstrom et al, 2009), while others argued for an involvement in anti-nociception of a descending modulatory pathway (Lin et al, 1996; Liu et al, 2002; Bardin et al, 2005; You et al, 2005; Colpaert et al, 2006). By using RT-PCR and Western blot, it was observed that both mRNA and protein levels of 5-HT1A receptors in the ipsilateral dorsal horn could be increased by subcutaneous bee venom injection.…”
Section: Nociceptive and Inflammatory Effects Of Subcutaneous Bee mentioning
confidence: 99%
“…The agonists were injected at 3 pharmacologically relevant doses to evaluate the influence of dose on glucose utilization and possible regional preferences of the drugs. The doses of 0.16 mg/kg to 0.63 mg/kg and the route of administration were chosen based on previous preclinical studies. Each rat was its own control and received each of the three doses of agonist and the saline solution in a randomized order. The interval between two acquisitions was at least 2 days, to ensure complete elimination of the molecules (the plasma half-life of NLX-112 in rat is about 1–2 h).…”
Section: Results and Discussionmentioning
confidence: 99%